2018
DOI: 10.1093/bioinformatics/bty877
|View full text |Cite
|
Sign up to set email alerts
|

SCALOP: sequence-based antibody canonical loop structure annotation

Abstract: Motivation Canonical forms of the antibody complementarity-determining regions (CDRs) were first described in 1987 and have been redefined on multiple occasions since. The canonical forms are often used to approximate the antibody binding site shape as they can be predicted from sequence. A rapid predictor would facilitate the annotation of CDR structures in the large amounts of repertoire data now becoming available from next generation sequencing experiments. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…In SAAB+, SCALOP annotates CDR-H1 and CDR-H2 sequences with structural canonical classes 22 , and FREAD predicts whether CDR-H3s from the Ig-seq data share a similar structure to a crystallographically-solved CDR-H3 structure 24 . We annotate predicted by FREAD the CDR-H3 sequence with the PDB code of the crystallographically-solved CDR-H3 structure (template).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In SAAB+, SCALOP annotates CDR-H1 and CDR-H2 sequences with structural canonical classes 22 , and FREAD predicts whether CDR-H3s from the Ig-seq data share a similar structure to a crystallographically-solved CDR-H3 structure 24 . We annotate predicted by FREAD the CDR-H3 sequence with the PDB code of the crystallographically-solved CDR-H3 structure (template).…”
Section: Resultsmentioning
confidence: 99%
“…To annotate the human and mouse data with structural information, we developed a customized version of our SAAB pipeline 15 , SAAB+ that predicts the structural shape of the IMGT-defined CDRs. CDR-H1 and CDR-H2 adopt a limited number of structural configurations, known as canonical classes 16,20,21 , which can be predicted accurately and rapidly from sequence 22 . SAAB+ uses SCALOP 22 to annotate non-CDR-H3 loop canonical classes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallographic studies have shown that antibody CDR-H1 and CDR-H2 loops can adopt a very limited number of structural conformations, known as canonical loop classes (37,38). These canonical classes are considered to be separate and distinct structures of the CDRs and can be rapidly and accurately annotated by SCALOP (23). The proportion of sequences in which either CDR-H1 and CDR-H2 had switched from the canonical class of their germline increased with age for most antigen-experienced subsets, similar to the increasing mutation number with age ( Figure 2C).…”
Section: Sequences With Predicted Antibody Structures Diverging From mentioning
confidence: 99%